There is life in the old horse yet or what else we can learn studying spin-1/2 XY chains - Derzhko, O. (Condensed Matter Physics, 2002)
We review some recent results on statistical mechanics of the one-dimensional
spin-1/2 XY systems paying special attention to the dynamic and thermodynamic
properties of the models with Dzyaloshinskii-Moriya interaction,
correlated disorder, and regularly alternating Hamiltonian parameters. Зроблено огляд деяких недавніх результатів з статистичної механіки одновимірних спін-1/2 XY систем. Особлива увага звернута на динамічні і термодинамічні властивості моделей з взаємодією Дзялошинського-Морія, скорельованим безладом і регулярно змінними параметрами гамільтоніана.